Conduction and induction heating - Davies, John 1926 October 7- (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1990)
Offers a theoretical and practical treatment of both conduction and induction heating, comprising four parts: conduction theory, induction theory, heat flow, and practice.
Electronic reproduction.
Keywords: Resistance heating; Induction heating; Electronic books